Mutations in TBL1X Are Associated With Central Hypothyroidism - Heinen, Charlotte A. (J Clin Endocrinol Metab, 2016)
CONTEXT: Isolated congenital central hypothyroidism (CeH) can result from mutations in TRHR, TSHB, and IGSF1, but its etiology often remains unexplained. We identified a missense mutation in the transducin β-like protein 1, X-linked (TBL1X) gene in three relatives diagnosed with isolated CeH. TBL1X is part of the thyroid hormone receptor-corepressor complex. OBJECTIVE: The objectives of the study were the identification of TBL1X mutations in patients with unexplained isolated CeH, Sanger sequencing of relatives of affected individuals, and clinical and biochemical characterization; in vitro investigation of functional consequences of mutations; and mRNA expression in, and immunostaining of, human hypothalami and pituitary glands. DESIGN: This was an observational study. SETTING: The study was conducted at university medical centers. PATIENTS: Nineteen individuals with and seven without a mutation participated in the study. MAIN OUTCOME MEASURES: Outcome measures included sequencing results, clinical and biochemical characteristics of mutation carriers, and results of in vitro functional and expression studies. RESULTS: Sanger sequencing yielded five additional mutations. All patients (n = 8; six males) were previously diagnosed with CeH (free T(4) [FT4] concentration below the reference interval, normal thyrotropin). Eleven relatives (two males) also carried mutations. One female had CeH, whereas 10 others had low-normal FT4 concentrations. As a group, adult mutation carriers had 20%–25% lower FT4 concentrations than controls. Twelve of 19 evaluated carriers had hearing loss. Mutations are located in the highly conserved WD40-repeat domain of the protein, influencing its expression and thermal stability. TBL1X mRNA and protein are expressed in the human hypothalamus and pituitary. CONCLUSIONS: TBL1X mutations are associated with CeH and hearing loss. FT4 concentrations in mutation carriers vary from low-normal to values compatible with CeH.